Optimization over Graphs - Suehyun Kwon (Center for Economic Studies and ifo Institute (CESifo), 2019)
This paper defines isomorphism for network formation that is not mathematically isomorphic. Once the pattern of network formation is characterized, one can test for (i) location fixed effects, (ii) heterogeneity, (iii) private information allowing for long-term contracts. The paper provides tests for directedness, heterogeneity, isomorphism and different types of stability.
Keywords: 330; networks; location fixed effects; path dependency